2021
DOI: 10.18632/aging.202682
|View full text |Cite
|
Sign up to set email alerts
|

Predicting lung adenocarcinoma prognosis with a novel risk scoring based on platelet-related gene expression

Abstract: Lung adenocarcinoma is the most common subtype of non-small cell lung cancer, and platelet receptor-related genes are related to its occurrence and progression. A new prognostic indicator based on platelet receptor-related genes was developed with multivariate COX analysis. Prognostic markers based on platelet-related risk score perform moderately in prognosis prediction. The functional annotation of this risk model in high-risk patients shows that the pathways related to cell cycle, glycolysis and platelet-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Our results showed that PFRGPS could effectively evaluate the prognosis and clinical status of patients with GC. Our model has higher accuracy than the previous prognostic models that have used PFRGs in tumor lung and breast cancers (Zhou et al, 2021;Xie et al, 2022). Nomograms are widely used for cancer prognosis (Balachandran et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…Our results showed that PFRGPS could effectively evaluate the prognosis and clinical status of patients with GC. Our model has higher accuracy than the previous prognostic models that have used PFRGs in tumor lung and breast cancers (Zhou et al, 2021;Xie et al, 2022). Nomograms are widely used for cancer prognosis (Balachandran et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…From the results, we observed that TP53, TTN, and MUC16 rank among the top 3 most frequently mutated genes in the corresponding cohorts. These genes were reported to be interactive and regulated various tumor associated biological processes ( Huang et al, 2021 ; Wu et al, 2021 ; Zhao et al, 2021 ; Zhou et al, 2021 ). We next investigated the co-occurring and exclusive mutation of the top 25 frequently mutated genes ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown attempts to establish models for predicting prognosis in patients with LUAD based on sequencing data and clinical features (Wang et al, 2020;Huang et al, 2021;Zhou et al, 2021). However, limited results have been applied in clinical practice.…”
Section: Discussionmentioning
confidence: 99%